LINGUOCOGNITIVE AND LINGUOCULTUROLOGICAL FEATURES OF COMPOSITE SENTENCES WITH AN INTRODUCTORY CLAUSE AS A VERBALIZER OF THE MICROCONCEPT "SUBJECTIVE–MODAL ASSESSMENT" IN LANGUAGE (Scientific journal of the Fergana State University, 2023)
This article touches upon the comparative analysis of the multilevel verbalizers of  the microconcept of  "subjective–modal assessment”, and  for the first time in English,  Uzbek and Russian their linguocognitive  field nature has been investigated, and the isomorphic and allomorphic features of the constituents  of the field have been revealed.